1987
DOI: 10.1111/j.1751-1097.1987.tb04848.x
|View full text |Cite
|
Sign up to set email alerts
|

TUMOR IMAGING WITH [111niIn]MONO‐DTPA‐ETHYLENEGLYCOL‐Ga‐DEUTEROPORPHYRIN

Abstract: Mono‐DPTA‐ethyleneglycol‐Ga‐deuteroporphyrin (MDEGD) was synthesized, by coordinating non‐radioactive Ga in the porphyrin ring and connecting DTPA (diethylene‐triamine‐N,N,N,N,N,‐pentaacetic acid) to its side chain. By labeling with 111In, chemicals for scintigraphy were developed. They were applied to Syrian golden hamsters with implanted pancreatic gland cancers and C57‐black mice with Lewis lung cancer to enable tumor imaging and biodistribution examination. A comparative study was also conducted with [67Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Fibrosarcoma tumour accumulation in Swiss mice was found to be 1.59 ± 0.52% ID/g with a T/B ratio of 8.56 ± 0.50 and T/M ratio of 26.5 ± 4.36 at 48 h. Tumour growth was retarded in treated animals, leading to a 68% decrease in tumour size after 8 days, following an initial dose of 92.5 MBq . A structurally similar agent has been prepared with a Gd‐labelled DOTA unit coupled to a porphyrin for potential multi‐functional magnetic resonance imaging/positron emission tomography (PET) imaging, and deuteroporphyrin, was previously functionalized to accommodate 111 In labelling using conventional chelating groups …”
Section: Bifunctional Chelatorsmentioning
confidence: 99%
“…Fibrosarcoma tumour accumulation in Swiss mice was found to be 1.59 ± 0.52% ID/g with a T/B ratio of 8.56 ± 0.50 and T/M ratio of 26.5 ± 4.36 at 48 h. Tumour growth was retarded in treated animals, leading to a 68% decrease in tumour size after 8 days, following an initial dose of 92.5 MBq . A structurally similar agent has been prepared with a Gd‐labelled DOTA unit coupled to a porphyrin for potential multi‐functional magnetic resonance imaging/positron emission tomography (PET) imaging, and deuteroporphyrin, was previously functionalized to accommodate 111 In labelling using conventional chelating groups …”
Section: Bifunctional Chelatorsmentioning
confidence: 99%
“…The DTPA ester of the metal-free 4-[1-(2-hydroxyethyloxy)ethyl]-2-vinyldeuteroporphyrin-IX (ATN-0), the Ga(III) complex (ATN-2), and Mn(III) complex (ATN-10) were chelated with 111 In and evaluated for tumor scintigraphy. The ATN-10 was included since the Mn(III) complex is not active as a photosensitizer and thus would avoid side effects such as skin photosensitivity. The synthetic steps involve hydrobromination of protoporphyrindimethylester to obtain a monobromoderivative, which upon treatment with ethylene glycol provides porphyrin 51 featuring an ether group at either the 7- or 12-position of the macrocycle.…”
Section: Radiolabeled Metalloporphyrins As Imaging Agentsmentioning
confidence: 99%
“…Animal studies showed good tumor uptake of 111 In−ATN-2 and 111 In−ATN-10, whereas 111 In−ATN-0 is essentially void of tumor localizing properties. A correlation between the nature of various substituents R on the dicarboxyporphyrin complex 54 and tumor accumulation in an animal model revealed that among over 200 derivatives, 111 In−hematoporphyrin glutamic acid, 111 In−monoDTPA-EG-Ga-DP, and 111 In−bisDTPA-EG-Ga-DP showed good tumor accumulation . Further modifications of the deuteroporphyrin IX side chains by replacing an ethylene glycol for a 2-vinyl group gave a derivative with optimal tumor selectivity …”
Section: Radiolabeled Metalloporphyrins As Imaging Agentsmentioning
confidence: 99%
“…Photosensitizers such as porphyrins have been the from the excited triplet state of the sensitizer, cb2 is given to be subject of intensive studies because of their poten-4 2 = ket [3021/(ket[3021 + kp) tial use for photodynamic therapy (PDT)? and diagnosis of tumors (Dougherty, 1983;Hayata el al., 1982;Kessel and Chou, 1983;Nakajima and Hayashi, 1984;Nakajima et al, 1987). Upon the photochemistry and photodynamic action of the photosensitizer in biological systems, there are two major mechanisms (Dougherty et al, 1978;Kessel, 1984;Moan, 1986): first, type I mechanism, in which the sensitizer molecules excited in the lower triplet state react directly with biological substrates to lead to cell-damages, and second, type I1 mechanism, the photogenerated triplet state of the sensitizer reacts with oxygen by an energy transfer process to produce singlet molecular oxygen, which in turn reacts with various biological substrates to injure the biological system.…”
Section: Introductionmentioning
confidence: 99%